Prognozowanie inflacji na podstawie pewnego modelu dynamicznego - Przybylska-Mazur, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Among more advanced models are the dynamic inflation models that describe the dynamic by means of stochastic differential equations. For the рurpose of the dynamic modeling of inflation, one can apply the Ornstein-Uhlenbeck process. This paper analyzes the forecasting of inflation on the grounds of the Ornstein-Uhlenbeck process applied in the one-factor model - the Vasicek model. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 332-338